RECENT ADVANCES OF CHOLINESTERASE INHIBITORS PLAYING A CRITICAL ROLE IN THE TREATMENT OF ALZHEIMER’S DISEASE (2020-2022) - Elmas Rumeysa Yıldırım; Nuray Ulusoy Güzeldemirci (Sabiad)
Alzheimer’s disease (AD) is a common neurodegenerative disorder which has a catastrophic effect on the brain. It significantly affects people’s daily life, especially the population over the age of 65, with problems such as neuron death, memory loss, cognitive disorders, and cholinergic dysfunction. However, despite the drug development studies which have been conducted recently quite intensively, an effective drug molecule that can completely cure people or stop the stage of the disease has not been found yet, unfortunately. One of the reasons for this is the complexity of understanding of how the pathology of the disease arises. The most accepted theory for AD is the cholinergic hypothesis. Acetylcholine (ACh), an important neurotransmitter, is metabolized by two cholinesterase (ChE) enzymes named acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). With AD, ChE activity increases and thus the degradation of acetylcholine is triggered. In addition, it is understood that the peripheral anionic region (PAS) of the AChE also caused the formation of Aβ-peptide fibrils. Therefore, based on this hypothesis, the most effective approach in treatment is the use of cholinesterase inhibitors (ChEI), which try to restore ACh levels by increasing them at cholinergic synapses. Furthermore, it focused on the design of multifunctional molecules. In conclusion, considering the complex nature of the disease and its effects, it is clear that more studies are needed in this area. In this study, important and remarkable studies in recent years have been included and it aimed to contribute to future drug research andv development studies.